PRAKTISI DAKWAH (RESOLUSI DA’I DALAM MENYIKAPI MASYARAKAT CYBER) - M. Sofiatul Iman (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2018)
The obligation of da’wah for every Muslim individual is an undeniable reality in order to improve the religion of the religious community and change from a bad living condition to a better life based on daily behavior on the Al-Quran and Sunnah, ijma ‘and qiyas. The success or failure of da’wah depends on how the message is delivered by the da’wah communicator (da’i) on the receiver (mad’u). But now the da’wah is faced with the reality of cyber society, the cyber community which is also called the global community gave birth to a variety of new cultures because of the freedom of unlimited interaction through the internet. It is necessary to have a resolution from the proselytizing practitioners, meaning that a da’I is not only required to be a vocalist in conveying his message of preaching, but is also required to be creative and innovative so that cyber society as mad’u can still be interested in the da’wah packaging delivered. With literature study approach and also mass media communication theory, this article is present to offer a resolution of a proselytizing practitioner in addressing cyber society as his mad’u. In this paper in the language about the method of da’wah that is associated with the relevance of cyber society, namely the method of da’wah in general in the Qur’an as a resolution. In other words, da’wah bilhikmah in cyber society, mau’idzatul hasanah in cyber society and al-mujadalah in cyber society. In addition, to support the effectiveness of da’wah in cyber society, an important component that must participate is the government, education environment and family environment.